Konservasi dan Rekam Jejak Musik Tradisional - Fransiskus Rendy, B. Com, M.A.B, Fransiskus Rendy, B.Com, M.A.B (Profilm Jurnal Ilmiah Ilmu Perfilman dan Pertelevisian, 2024)
Audio and visual recording through technology plays a central role in the conservation of traditional music. Various strategies, such as reproducing the sound of traditional musical instruments, documenting playing techniques, and involving education and training, are important elements of conservation efforts. Dissemination through digital archives, promotion of cultural identity, and ethnomusicological research are also integral partsof the program. However, a few challenges such as lack of facilities and infrastructure, the threat of loss of cultural heritage, and intellectual property rights issues need to be addressed. How can audio productiontechnology be used to record, preserve, and document traditional music that may be endangered? How can audio production contribute to the preservation of traditional musical heritage? The research method used toinvestigate both problems is qualitative research method. The result of this research is that it can be through a collaborative approach with governments, non-profit institutions, and the private sector, including increasing access, education, and training, developing sustainable sources of funds, and managing intellectual property rights. The involvement of the younger generation is an important focus in ensuring the continuity of traditional music preservation. Involving them in the production process, supporting creative experimentation, and incorporating traditional music material in the formal education curriculum are key steps. All of them aim to maintain the relevance of traditional music during globalization and modernization. With technological, cultural, and legal literacy, as well as through strong collaboration from various stakeholders, it is hoped thattraditional music conservation efforts can be technically successful and sustainable, preserving Indonesia's cultural wealth for future generations.